2021
DOI: 10.1002/anie.202105312
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Tailoring in Luzopeptin Biosynthesis Involves Cytochrome P450‐Mediated Carbon–Nitrogen Bond Desaturation for Hydrazone Formation

Abstract: Luzopeptins and related decadepsipeptides are bisintercalator nonribosomal peptides featuring rare acylsubstituted tetrahydropyridazine-3-carboxylic acid (Thp) subunits that are critical to their biological activities.H erein, we reconstitute the biosynthetic tailoring pathwayinluzopeptin A biosynthesis through in vivo genetic and in vitro biochemical approaches.S ignificantly,w er evealed am ultitasking cytochrome P450 enzyme that catalyzesf our consecutive oxidations including the highly unusual carbon-nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 35 publications
0
21
1
Order By: Relevance
“…In contrast to the omnipresence of synthetic hydrazones, only a small number of naturally occurring hydrazones are known today (Scheme S1). Several low-molecular-weight hydrazones, such as farylhydrazones and prolinimines, were isolated from fungi, plants, and other eukaryotes as early as 1967. , Hydrazones are also known to be produced by prokaryotes as exemplified by the Streptomyces-produced yoropyrazone, katorazone, S56-p1, and luzopeptins/korkormicins. The biosynthetic studies on S56-p1 and luzopeptins revealed the formation of hydrazone via the oxidation of hydrazine intermediates, whereas some other natural hydrazones are speculated to be generated by hydrazine–ketone condensation. , …”
Section: Introductioncontrasting
confidence: 66%
See 4 more Smart Citations
“…In contrast to the omnipresence of synthetic hydrazones, only a small number of naturally occurring hydrazones are known today (Scheme S1). Several low-molecular-weight hydrazones, such as farylhydrazones and prolinimines, were isolated from fungi, plants, and other eukaryotes as early as 1967. , Hydrazones are also known to be produced by prokaryotes as exemplified by the Streptomyces-produced yoropyrazone, katorazone, S56-p1, and luzopeptins/korkormicins. The biosynthetic studies on S56-p1 and luzopeptins revealed the formation of hydrazone via the oxidation of hydrazine intermediates, whereas some other natural hydrazones are speculated to be generated by hydrazine–ketone condensation. , …”
Section: Introductioncontrasting
confidence: 66%
“…Surprisingly, the N-H (δ H 10.32) and vinyl methyl (δ H 1.89 and δ C 10.1) signals are reminiscent of the unique arylhydrazone unit in the fungal metabolite farylhydrazones (Scheme S5). 8 The presence of the arylhydrazone functionality, along with the adjacent three-carbon linker (C1−C3), was further substantiated by the 1 H− 15 N HSQC and 1 H− 13 C/ 15 N HMBC correlations (Figure 1C and Figures S2-10 and S2-12). The presence of the unusual arylhydrazone, the hydroxylated and methylated cyclic pentapeptide scaffold, and the lipophilic AHA chain distinguishes 1−3 from other currently known cyclic peptides.…”
Section: ■ Resultsmentioning
confidence: 81%
See 3 more Smart Citations